Tyler Perry's Madea's big happy family - Perry, Tyler; Cannon, Reuben, 1946-; Bobb, Roger M., 1967-; Bow Wow (Musician); Mann, David, 1966-; Devine, Loretta; Davis, Cassi, 1964-; Mann, Tamela; Perry, Rodney; Kane, Shannon; Lions Gate Films (Santa Monica, Calif.); Tyler Perry Studios (Firm) (Santa Monica, Calif. : Lionsgate, 2011)
Madea, everyone's favorite wise-cracking, take-no-prisoners grandma, jumps into action when her niece, Shirley, receives distressing news about her health. All Shirley wants is to gather her three adult children around her and share the news as a family. It's up to Madea, with the help of the equally rambunctious Aunt Bam, to gather the clan together and make things right the only way she knows how: with a lot of tough love, laughter, and the revelation of a long-buried family secret.
Originally released as a motion picture in 2011.
Special features: "Byreeen", the baby mama from hell ; Ties that bind ; Madea's family tree ; Brown calls Maury.
Director of photography, Toyomichi Kurita ; editor, Maysie Hoy ; music, Aaron Zigman.
Loretta Devine, Shad 'Bow Wow' Moss, David Mann, Cassi Davis, Tamela Mann, Lauren London, Isaiah Mustafa, Rodney Perry, Shannon Kane, Tyler Perry.
MPAA rating: PG-13, for drug content, language, and some mature thematic material.
DVD; region 1, widescreen (1.78:1, 16x9) presentation; Dolby Digital 5.1.
Keywords: African American families -- Drama; Families -- Drama; Family secrets -- Drama; Comedy films; Feature films; Video recordings for the hearing impaired; Comedy films; Feature films